2021
DOI: 10.7759/cureus.20564
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Complications in Crohn's Disease Patients: Factors, Pathogenesis, and Treatment Outlines

Abstract: The causes of osteoporosis in Crohn's disease (CD) are multifactorial; cytokines, steroids, and vitamin deficiency all have an essential role. It is imperative to distinguish the factors that contribute to bone resorption, potentially increasing the risk of low bone mineral density (BMD), osteoporosis, and fracture. However, the pathogenicity of osteoporosis associated with CD remains unclear. Although osteoporosis treatment may vary between bisphosphonate and corticosteroid, infliximab's efficacy, when combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Previously, we found that a dysregulated pro-inflammatory cytokine level caused by MAP infection results in an extraintestinal manifestation characterized by hyperactive osteoclast activity, which eventually affects bone biomarker levels such as osteocalcin and calcium among CD patients [26]. Additionally, the prevalence of osteoporosis is higher among inflammatory bowel disease patients in general, and some relatively young patients have been diagnosed with severe cases of bone disorders [27].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found that a dysregulated pro-inflammatory cytokine level caused by MAP infection results in an extraintestinal manifestation characterized by hyperactive osteoclast activity, which eventually affects bone biomarker levels such as osteocalcin and calcium among CD patients [26]. Additionally, the prevalence of osteoporosis is higher among inflammatory bowel disease patients in general, and some relatively young patients have been diagnosed with severe cases of bone disorders [27].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of protein, loss of muscle mass due to steroids, poor diet, and poor absorption of nutrients cause weight loss and malnutrition [7,9,18]. Insufficient intake and poor absorption of calcium, deficiency of vitamin D, reduced physical activity, inflammation, long term corticosteroids result in decreased bone formation and mineralization [19]. Our patient was diagnosed with low bone density and osteoporosis, so regular diagnostic monitoring with DEXA (dual-energy x-ray absorptiometry) was introduced.…”
Section: Case Reportmentioning
confidence: 96%
“…Extraintestinal symptoms and signs are ulcers or sores in the mouth [18], osteoporosis is more common [19], due to inflammation, impaired absorption of iron from the small intestine (malabsorption), and recurrent bleeding. Anemia is often present.…”
Section: Case Reportmentioning
confidence: 99%
“…TNF-α blockade improves bone formation and reduces bone resorption by suppressing T cells [16,17]. Infliximab maintenance therapy also leads to about a 14% increase in lumbar bone density [18,19]. The Swiss IBD cohort study (SIBDCS), launched in 2006 with the aim of enrolling and following patients with IBD throughout Switzerland [20], demonstrated that early administration of anti-TNF-α was associated with a lower osteoporosis risk.…”
Section: Pathophysiology Of Inflammatory Bowel Disease-associated Bon...mentioning
confidence: 99%